Recent progress of research on anti‐tumor agents using benzimidazole as the structure unit. (9th February 2022) - Wu, Kaiyue; Peng, Xiaoyu; Chen, Miaojia; Li, Yang; Tang, Guotao; Peng, Junmei; Peng, Yuanyuan; Cao, Xuan
Abstract: With the development of exploration for disease‐related proteins or receptors, more and more novel structural lead compounds are required to designed and synthesized. The benzimidazole is an effective structural unit in which the benzene ring is fused at the 4 and 5 positions of the imidazole ring and wildly used in drug design. Here, we introduce some recent progress of research for anti‐tumor agents which was target to various target proteins such as DNA topoisomerase, angiogenesis, serine/threonine protein kinase, and tyrosine protein kinase. These anti‐tumor agents are all introduced benzimidazole as the structure unit. Further docking study showed that the benzimidazole group was not only act as a skeleton to expand the structure of molecule but also as an excellent ligand unit to form hydrogen bond or π–π conjugation and hydrophobic interaction with target proteins or receptors. We expect that introducing benzimidazole in the chemical structure could be a reasonable and priority strategy in novel anti‐tumor agents' design. Abstract : We introduced some recent progress of research of benzimidazole for anti‐tumor agents which was target to various target proteins such as DNA topoisomerase, angiogenesis, serine/threonine protein kinase, and tyrosine protein kinase.